Mechanism of retrograde transport in contact-dependent inhibition (CDI) toxins through the bacterial translocon - Kruglhuber, Anna (Jihočeská univerzita, 2023)
Amongst bacteria, living in complex and varying communities and surroundings, rivalry for crucial resources exists. Due to the constant pressure, strategies to allow competition and communication have been developed within bacterial communities. In this respect, Contact Dependent Growth Inhibition (CDI) is often of relevance. The aim was to elucidate a newly found pathway of transport of the CDI toxins across the inner bacterial membrane via Sec translocon. Since all proteins are transported via Sec translocon in an unfolded state, and there is no obvious mechanism which would drive or facilitate this transport in the retrograde fashion, the hypothesis that the effector domain of CDI toxins evolved an anisotropic energy landscape of mechanical unfolding was constructed. That would allow the toxin to be mechanically more labile in the direction of translocation and mechanically stable in the orthogonal directions. This anisotropy would permit efficient translocation and overall thermodynamic stability at the same time. The unfolding landscape was assessed by a molecular dynamics simulation combined with umbrella sampling. Developed methodology, complemented with a rational design of "circular permutants", helped to estimate the forces required to unfold the toxins under different geometries.
Mechanism of retrograde transport in contact-dependent inhibition (CDI) toxins through the bacterial translocon
Keywords: contact-dependent inhibition (CDI); SecYEG translocon; molecular dynamics simulations; CdiA toxin; anisotropy; mechanical unfolding; retrograde translocation mechanism; contact-dependent inhibition (CDI); SecYEG translocon; molecular dynamics simulations; CdiA toxin; anisotropy; mechanical unfolding; retrograde translocation mechanism